Pooled Sequencing Analysis of Geese (Anser cygnoides) Reveals Genomic Variations Associated With Feather Color - Ren, Shuang; Lyu, Guangqi; Irwin, David M.; Liu, Xin; Feng, Chunyu; Luo, Runhong; Zhang, Junpeng; Sun, Yongfeng; Shang, Songyang; Zhang, Shuyi; Wang, Zhe (Frontiers in Genetics, 2021)
During the domestication of the goose a change in its feather color took place, however, the molecular mechanisms responsible for this change are not completely understood. Here, we performed whole-genome resequencing on three pooled samples of geese (feral and domestic geese), with two distinct feather colors, to identify genes that might regulate feather color. We identified around 8 million SNPs within each of the three pools and validated allele frequencies for a subset of these SNPs using PCR and Sanger sequencing. Several genomic regions with signatures of differential selection were found when we compared the grey and white feather color populations using the FST and Hp approaches. When we combined previous functional studies with our genomic analyses we identified 26 genes ((KITLG, MITF, TYRO3, KIT, AP3B1, SMARCA2, ROR2, CSNK1G3, CCDC112, VAMP7, SLC16A2, LOC106047519, RLIM, KIAA2022, ST8SIA4, LOC106044163, TRPM6, TICAM2, LOC106038556, LOC106038575, LOC106038574, LOC106038594, LOC106038573, LOC106038604, LOC106047489 and LOC106047492) that potentially regulate feather color in geese. These results substantially expand the catalog of potential feather color regulators in geese and provide a basis for further studies on domestication and avian feather coloration.